ChemInform Abstract: Copper‐Catalyzed Oxidation of Deoxybenzoins to Benzils under Aerobic Conditions. Issue 41 (19th September 2013) - Cacchi, Sandro; Fabrizi, Giancarlo; Goggiamani, Antonella; Iazzetti, Antonia; Verdiglione, Rosanna
Abstract The process proceeds under neutral conditions using air as the oxidant and is tolerant to various functional groups.